Can we 'WaSH' infectious diseases out of slums?. (March 2020) - Ross, Allen G.; Rahman, Mahbubur; Alam, Munirul; Zaman, K.; Qadri, Firdausi
Highlights: The world is becoming increasingly urban, with most of this growth occurring in slums of the developing world. The burden of infectious diseases is high in slums, particularly enteric diseases transmitted fecal-orally. Water, santation and hygiene (WaSH) will need to be combined with vaccination and/or treatment when available if sustainable control of infectious diseases in slums is to be achieved. Abstract: The world is becoming increasingly urban and most of this growth is taking place in urban slums of the developing world. The current (2019) global population stands at 7.7 billion, with approximately one billion (13%) living in urban slums. By 2030 the world's population is projected to grow to 8.5 billion, with an estimated two billion (24%) living in slums. Slums are typically overcrowded, with most residents sharing a single room with four to five family members. There is usually no formal sewage or waste disposal system. Open sewage, with antimicrobial-resistant organisms, typically flows just outside the door, which during the rainy season often enters the home and contaminates the household drinking source. Hygiene is difficult if not impossible to maintain, hence the significant burden of infectious diseases, especially those with a faecal–oral mode of transmission. Transmission is year-round and the leading enteric pathogens are rotavirus, Cryptosporidium, S higella, Campylobacter, Salmonella typhi, and Vibrio cholera . Water, sanitation, and hygiene (WaSH) will be crucial components of a future integrated control strategy for infectious diseases in slums. Cheap WaSH interventions have been trialled, but their impact has been modest and short-lived. More expensive WaSH alternatives that will provide lasting change now need to be explored. Can we 'WaSH' infectious diseases out of slums?